The Relationship between Poverty and Unemployment in Niger State - Umar Faruk Mohammad; Joseph David (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2019)
The nature of the relationship between the twin problem of poverty and unemployment has been unclear recently. Although the nature of the relationship has received more extensive scholarly attention worldwide and even in Nigeria, no study raised on the nature of its relationship in the region (state) which might produce an inverse relationship different from the proportionate obtained in previous studies. Hence the study on the relationship between poverty and unemployment in Niger state, Nigeria, using descriptive and a logistics regression model to analyze the 102 cross-sectional data randomly collected from the three geopolitical regions in the state. The result thus shows the existence of a proportionate relationship between poverty and unemployment, following the pattern of previous studies. The study thus recommends the actions of the policymakers in creating vocational skill programs to the aid-curb unemployment problem in the state. Accordingly, the increase in expenditure on education and the minimum wage as well recommended.